2009
DOI: 10.1111/j.1478-3231.2009.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 promoter polymorphisms in hepatitis C patients with and without Schistosoma mansoni co‐infection

Abstract: Our findings suggest that common IL-10 (-1082, -819 and -592) genotypes/haplotypes do not influence the degree of HAI and response to combination therapy or susceptibility to HCV infection with and without S. mansoni co-infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…However, we did not observe any association between IL-10 polymorphisms with S. haematobium and P. falciparum co-infections in this study. This is in agreement with previous findings indicating that these three IL-10 promoter variants are not associated with susceptibility to hepatitis C virus infection with and without S. mansoni co-infection [33].…”
Section: Discussionsupporting
confidence: 93%
“…However, we did not observe any association between IL-10 polymorphisms with S. haematobium and P. falciparum co-infections in this study. This is in agreement with previous findings indicating that these three IL-10 promoter variants are not associated with susceptibility to hepatitis C virus infection with and without S. mansoni co-infection [33].…”
Section: Discussionsupporting
confidence: 93%
“…The details of the discrepancy in the results between IL-10 gene polymorphisms and IFN anti-viral response are still unknown. Abbas et al (37) suggested that the recent IFN treatment strategies including IFN modifications (recombinant and PEGlyated), the duration of treatment, and combination with ribavirin administration might affect the results of these studies. For example, ribavirin administration promotes Th1 lymphocytes and suppresses IL-10 production (38).…”
Section: Discussionmentioning
confidence: 99%
“…[2] of a high response among Egyptian patients with schistosomiasis despite the presence of more severe fibrosis. Increased susceptibility to HCV in schistosomiasis patients because of increased production of IL‐10 is no longer accepted [21]. The reported normal thrombopoietin [22] and elevated von Willebrand factor antigen [23] levels in schistosomiasis may explain the absence of thrombocytopenia as an adverse effect in our patients with bilharzial coinfection.…”
Section: Discussionmentioning
confidence: 90%